Exposure of chlorpyrifos in toddlers living in an agricultural area in Sakon Nakhon province, North-East Thailand. Issue 2 (11th March 2019) - Siriwat, Satinee; Rohitrattana, Juthasiri; Nganchamung, Thitirat; Ong-artborirak, Parichat; Robson, Mark; Siriwong, Wattasit
Abstract : Purpose: Children living in agricultural areas are exposed to pesticides in their living areas and through activities of daily living. These exposures may lead to adverse health effects. The purpose of this paper is to investigate household environmental and behavioural factors associated with chlorpyrifos exposure and resultant adverse health effects in children living in an agricultural community. Design/methodology/approach: A cross-sectional study was conducted including 65 toddlers (age of 12–36 months) and their parents were face-to-face interviewed from January to February 2016. Toddler's hands and feet, toys and floors were wiped for chlorpyrifos residue analysis. The wipes were extracted and analysed by gas chromatography with a flame photometric detector, and blood cholinesterase activity was measured by the EQM Test-mate (model 400). Findings: The average age (± standard deviation) of children was 19.9 (±5.9) months. Chlorpyrifos detections were 61.5 per cent (hands), 57.1 per cent (toys), 53.8 per cent (floors) and 30.8 per cent (feet). The highest chlorpyrifos residue concentration was detected on toy surface (3.022 µg/m 2 ). Chlorpyrifos residues on hands and feet were positively correlated with concentrations on floors and toys (Spearman's ρ, p <0.01). Multiple linear regression analysis revealed that more frequent hand washing ( β =−0.236, p =0.067) and showering ( β =−0.240, p =0.056) was negatively associated with chlorpyrifos residue on children's body. House cleaning frequency was significantly associated with an increase in haemoglobin-adjusted erythrocyte cholinesterase ( β =0.251, p <0.05). Originality/value: Chlorpyrifos exposures found in the children household area through their activities and behaviours can cause several adverse health effects. The circumstances associated with chlorpyrifos exposure should be mitigated and reduced to improve the household environment of children living agricultural areas.